In response to the Letter to the Editor by Dr AA. Zulfiqar re our publication “Multidimensional Short Tools to Assess Frailty: a Narrative Review” (Ann Ig. 2022 Mar 18. doi: 10.7416/ai.2022.2516. Online ahead of print) - Formosa, V.; Lorusso, G.; Lentini, G.; Terracciano, E.; Gentili, S.; Liotta, G. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
We appreciate that Dr. Zulfiqar showed us that they had already demonstrated the validity and reliability of his ZFS scale. Still, it is evident that, in our paper, we could not take it for granted because all the articles they quote have been published after we handed out ours to the Managing Editor of Ann Ig.